P-015 YI Incidence of Hospital Acquired Conditions (HACs) in Patients Admitted with Inflammatory Bowel Disease (IBD): A Nationwide Population-Based Study. (March 2016) - Obi, Kenneth; Hinton, Alice; Levine, Edward; Zhang, Cheng
Abstract : Background: IBD is common among Western populations and the socioeconomic burden of the disease is significant. In 2008, the Centers for Medicare and Medicaid Services (CMS) selected 10 categories of conditions that were deemed as HACs, ranging from falls to vascular catheter-associated infection. Costs related to HACs are not reimbursed as they are considered to be preventable. The effect of this change in reimbursement on the incidence of HACs among patients hospitalized with IBD is unknown. Methods: This was a cross-sectional study using data from the Nationwide Inpatient Sample (NIS, 2007–2011). IBD hospitalizations and HACs were identified using appropriate ICD-9-CM codes. We excluded patients under the age of 19 and those who carried the diagnoses of both UC and CD. We excluded HACs that were related to surgical procedures. The presence of HAC was defined as having at least one qualifying complications as listed by the CMS. HAC incidence in patients with UC or CD was evaluated according to health insurance. All analyses were conducted with SAS, version 9.3, Cary, NC. Results: From 2007 to 2011, there were a total of 347, 577 discharges related to CD; of those, 1, 222 experienced at least 1 HAC. The overall HAC incidence rate for CD patients was 0.35%. There has been a slow upward trend in the incidence of HACs since 2007 from 0.18% to 0.42% in 2011 ( P ⩽ 0.0001). This trend was significant in Medicare, Medicaid and private insurance patients alike. HACs disproportionately affected Medicare patients during the time period compared with Medicaid or private patients (incidence 0.74% versus 0.24% or 0.21%, respectively). However, on multivariate analysis, there was no significant difference between the groups. During the time period, there were 188, 125 UC discharges with 1, 068 patients experiencing HACs and an incidence rate of 0.57%. There was an overall increase in incidence of HACs from 2007 to 2011 ( P = 0.0027). UC patients on Medicare had higher rates of HACs compared with Medicaid or private patients (1.25% versus 0.46% and 0.21%, respectively). After adjusting for confounders, the odds ratio for experiencing HACs was 2.91 for Medicare patients and 2.56 for Medicaid patients, compared with private insurance holders ( P < 0.0001). Conclusions: There was no appreciable decline in the incidence of HACs across U.S. hospitals in the years following implementation of the CMS non-reimbursement policies. In fact, there has been increased reporting of HAC occurrences over the examined period. IBD, especially UC, patients on Medicare have the highest risk of experiencing a hospital-acquired complication, which may be related to older age. Heightened awareness is required to understand and address this disparity.